2020
DOI: 10.1111/imb.12653
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the role of Rhodnius prolixusCYP4G genes in straight and methyl‐branched hydrocarbon formation and in desiccation tolerance

Abstract: Insect cuticle hydrocarbons are involved primarily in waterproofing the cuticle, but also participate in chemical communication and regulate the penetration of insecticides and microorganisms. The last step in insect hydrocarbon biosynthesis is carried out by an insect‐specific cytochrome P450 of the 4G subfamily (CYP4G). Two genes (CYP4G106 and CYP4G107) have been reported in the triatomines Rhodnius prolixus and Triatoma infestans. In this work, their molecular and functional characterization is carried out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…They are quite common in terrestrial insect species from dry areas [ 47 ] and the predominant class of CHCs in desert Tenebrionidae, with an exceptionally thick and impermeable epicuticular wax layer, and generally with more carbon atoms than n-alkanes [ 48 ]. In addition, a recent study showed that a gene related to the synthesis of methyl-branched hydrocarbons is a determinant for the waterproofing properties of Rhodnius prolixus cuticle under desiccation [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…They are quite common in terrestrial insect species from dry areas [ 47 ] and the predominant class of CHCs in desert Tenebrionidae, with an exceptionally thick and impermeable epicuticular wax layer, and generally with more carbon atoms than n-alkanes [ 48 ]. In addition, a recent study showed that a gene related to the synthesis of methyl-branched hydrocarbons is a determinant for the waterproofing properties of Rhodnius prolixus cuticle under desiccation [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that CYP4 family plays a role in insecticide tolerance and resistance in triatomine species, given their higher expression in T. infestans resistant to pyrethroids [ 4 , 21 ]. Moreover, RNAi mediated gene-silencing of some CYP4 family members led to an increased susceptibility to deltamethrin in T. infestans [ 22 ] and R. prolixus [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Even in the presence of acetone only (no insecticide), dsCYP4EM1-injected insects presented reduced LT 50 (104 days) compared with dsKer-injected bugs (148 days). Dulbecco et al (2020) showed that two genes also belonging to the CYP4 clade (CYP4G106 and CYP4G107), which are expressed mainly in R. prolixus integument, are related to cuticle formation and dehydration process. Thus, dsCYP4EM1 injection in addition to CY4PEM2 co-silencing could potentially reduce the expression of different CYP4s clade genes (as observed for CYP4EM3).…”
Section: Discussionmentioning
confidence: 99%